Shear strengthening of masonry wallettes resorting to structural repointing and FRCM composites - Casacci, Susanna (2019)
Results of an experimental campaign conducted on plain and reinforced masonry wallettes subjected to diagonal compression tests are presented in this paper. The masonry panels were reinforced by means of two strengthening techniques: structural repointing achieved by inserting basalt bars in the mortar bed joints and fiber reinforced cementitious matrix (FRCM) composite, obtained by applying a single-ply glass mesh on the sides of the specimens. The structural effects of symmetric and asymmetric strengthening configurations are investigated. The main mechanical parameters, such as shear capacity, ductility and shear modulus, are compared and discussed introducing a calibrated reinforcement ratio. Further, analytical procedures presented in the codes and in literature are followed to predict the shear capacity of the unstrengthened and strengthened wallettes and, finally, compared to the values obtained experimentally.